GALERI SENI DAN BUDAYA TORAJA DENGAN PENERAPAN ARSITEKTUR FUTURISTIK DI TORAJA UTARA SULAWESI SELATAN INDONESIA - Freike Eugene Kawatu; martha masakke, rachelbatara; M. Y. Noorwahyu Budhyowati (TEKTONIK : Jurnal Ilmu Teknik, 2025)
Toraja is an icon of cultural arts and tourism in South Sulawesi Province which has a high attraction in the Indonesian tourism industry because of its uniqueness. Based on tourism data, visitors from inside and outside have increased, but due to various limitations and problems related to the existence of Toraja Art and Culture, many are difficult to access and lack of land utilization as well as the utilization of the influence of existing technology to be a bad influence on cultural arts which actually affects the number of tourists to decline, considering the potential influence of the Toraja problem, the author needs a special place to accommodate Cultural Arts activities with the aim of increasing attractiveness, making it easier for tourists and the wider community to access Cultural Arts without having to eliminate the original Cultural Arts. Responding to the existing problems, the author designed the Art and Culture Gallery with the application of Futuristic Architecture where Futuristic Architecture is an architectural style that is not simple and is even famous for its unique dynamic shape and is also known for the application of various sophisticated technologies in its design, Therefore the use of futuristic architecture in this design is expected to be able to make the Toraja Art and Culture gallery a place that has a strong attraction that can also meet the needs of artists and tourists and can provide an overview of the harmony of technology with art and culture that can be utilized according to the development of modern times, in other words it can be concluded that technology does not always damage art and culture but on the contrary technology can be a developer tool through promotion as well as a tool that can store the history of Toraja Art and culture.